Influence of Bamboo Biochar and Gibberellic Acid on Vegetative and Flower Production of Tagetes erecta L. - Pareekhan Nasir Kanaby; Sawsan Mohammed Saeed (Zanco Journal of Pure and Applied Sciences, 2022)
This research was carried out in open field Grdarasha, Agriculture College, Salahaddin University through March 18th to August 21th 2021 to study the effects of Bamboo biochar (0, 3, 6 and 9 ton.ha-1) as soil application and foliar spray GA3 (0, 200, 400 ml.l-1) on (Tagetes erecta L.) vegetative growth and flowering. The maximum number of leaves.plant-1, number of branches plant-1, vegetative growth dry mass (511.24, 61.82 and 115.63g) were observed from 9 ton.ha-1 of Bamboo biochar, and the highest stem diameter (22.31mm) was recorded from 6 ton.ha-1 of Bamboo biochar. However, the maximum values of number of leaves per plant (502.20), plant height (54.00 cm) and vegetative growth dry weight (109.09 g) were recorded in a higher GA3 concentration 400 ml.l-1. The interaction treatment of 6 ton.ha-1 of Bamboo biochar and 400 ml.l-1 GA3 gave the highest value of plant height and stem diameter (55.83 cm and 24.00 mm respectively). The best result time to reach %50 flowering (55.00 days) was obtained from 3 ton.ha-1 of Bamboo biochar, and the best results of time to reach 50% flowering (55.83 days), number of flowers per plant(46.02) and number of flowers per plot(184.08) were obtained from 400 ml.l-1 of GA3. The interaction treatment of 400 ml.l-1 of GA3 without Bamboo biochar gave the highest of number of flowers per plant (57.58), number of flowers per plot (230.33), flowers fresh weight per plant (212.17 g), flowers fresh weight per plot (848.67 g) and flowers fresh weight per hectar (7.07 ton).